Orbital debris requires prevention and mitigation across the satellite life cycle - Mia M. Bennett (Communications Engineering)
Satellites are crowding orbital space, particularly Low Earth Orbit, exacerbating the risk of orbital debris. Here, measures across the satellite life cycle are recommended to promote space sustainability including stronger regulations, fiscal and market-based interventions, multilateral institutions, and active debris removal.